Learn Mandarin in 28 hours with award-winning book - Joash EE, De Silva (The Star Publications (M) Berhad, 2017)
PEKAN: Can you learn Mandarin in 28 hours? Yong Ying Mei's book "Mandarin For All", aims to helps non-Mandarin speaking students learn the language in that time so they will be able to sit for the Hanyu Shuiping Ka oshi (HSK) test.